ONLINE PERSPECTIVES ON ASEAN-JAPAN RELATIONS: Study of ASEAN-related Japanese Tweets - Pratidina, Indah Santi (Center for Southeast Asian Social Studies (CESASS), 2018)
ASEAN targets internal integration and strong external relations with its partner countries. Japan has stressed its long-standing support for ASEAN. The year 2013 saw the 40th anniversary of Japan-ASEAN relations when Japanese state actors put considerable efforts into marking this anniversary. Although Japan remains one of ASEAN's largest trading partners and sources of foreign direct investment, recent years has witnessed power relations dynamic in the region with China and South Korea actively engaging as well. State actors? statements on ASEAN-Japan relations had been the heavy focus of scholars interested in the field. However, insights from all levels of society are important for a more comprehensive observation. An analysis of social media, and in particular Twitter, offers one way to accomplish this purpose. The total of 3.29 million tweets containing the word ?ASEAN? were collected from November 2013 to December 2015. From the dataset, it was identified that tweets using Japanese language are the third highest in volume after Indonesian and English. Content analyses were conducted to answer the questions on how ASEAN as an entity is viewed by the populations of its partner countries; which aspects of the integration project attract Twitter users? interests also, in the relation to strong external relations that ASEAN want to pursue, which countries are mentioned in the tweets and on which aspects? Using keywords from the Blueprints of ASEAN Community?s integration aspects, the tweets were categorized as related to economics, political-security and socio-cultural topics. Countries mentioned in the dataset were counted and then categorized according to these aspects as well. The study finds economic and political-security themed tweets are the largest in volume with heavy mentioning of Japan, China and South Korea. Results suggest that online conversations about ASEAN are still strongly influenced by government and mainstream media?s agenda.